Cuidados de enfermería en complicaciones clínicas y metabólicas en pacientes diabéticos que acuden al Hospital Sagrado Corazón de Jesús. Quevedo, Los Ríos, octubre 2018 - abril 2019 - De Luca Macias, Maria Magdalena (2019)
Introduction. Diabetes mellitus is a disease that is accompanied by alterations in the metabolism of lipids and proteins, which leads to microvascular and macrovascular involvement that affects different target organs. General objective. To determine nursing care in clinical and metabolic complications in diabetic patients who come to the Sacred Heart of Jesus Canton Quevedo Hospital, Los Ríos province in the period from October 2018 to April 2019. Methodology. The research had a qualitative-quantitative approach, field study, exploratory and descriptive, for the purpose was applied and not experimental cross-sectional. Unscientific scientific observation and the survey were used; A questionnaire was applied as an instrument. The universe of 102 patients and the sample were 55 diabetic patients, sampling was intentional non-probabilistic. Results. Age group over 65 years old (38.1%), female (54.4%), housewife (63.6%). 69.8% do not know standing self-care techniques, 70.9% do not receive foot exploration by health personnel, nursing care is fulfilled in more than 50%, 63.6% have suffered metabolic complications: hyperglycemia 68.5%) and 47.2% chronic complications: nephropathy (65.3%). Conclusions. Sociodemographic profile characterized by over 65s. Hyperglycaemia, nephropathy were the most prevalent clinical and metabolic complications. The main nursing care in diabetic patients should be considered as the whole and part of comprehensive and continuous diabetes care